SIGNIFIKAN PENDIDIKAN SIVIK TERHADAP PENGUKUHAN PROSES DEMOKRASI DI THAILAND - Panaemalae, Abdulrazak @ Abdulroya (Journal of Techno-Social, 2016)
This article will discuss on the development of civic education and it contribution towards the democratization in Thailand. The aim is to highlight the weakness of democratic system that is practiced which is seemed originated from the lack of emphasis on the civic education. Furthermore, it will support and argue the important of such education as a mechanism in enhancing the democratization process. The formation of democratic country of Thailand started since 1932. The unfinished formation gone through the stages of continously up and down in the process. Theoretically, the process deserve a recognition. It is going into the right direction of having the ideal democratic country. There were continuous efforts between government and the people to cooperate to ensure the formation of an intent democratic country accomplished. However, in reality they are ample of evidence showing that the practice of democracy is facing problems, whereby people feels that there is less democracy in the country which claim as a democratic. The development of democratic country is facing many hurdles, and among the main one is the lack of awareness by the people on their responsibilities towards establishing a democratic system. Furthermore, it interrupt the formation of the country of intent, and there are people look at Thailand as less successful in practicing the principles of democracy as it should be.Therefore, the needs of civic education to be thought to the people in order to establish a successful democratic country. The concern is arising among the Thai elites lately. In addition, the curriculum of civic education need to be evaluated to include the basic principles of democracy, also the rights and obligations under that principles, so people could practice it accordingly.